Transplantation of embryonic nervous tissue influence on epileptogenesis at the patients with apallic syndrome and its consequences - Tsymbalyuk, V. I.; Latyshev, D. Yu.; Pichkur, L. D. (Ukrainian Neurosurgical Journal, 2005)
We represent the analysis of 64 patients with apallic syndrome (AS) clinical state. These patients were treated by embryonic nervous tissue transplantation (ENT). The dynamic of clinical course of convulsive syndrome is considered. It was established that at 60,9% patients the course AS was complicated by the epileptic attacks origin (EA). On the origin of epileptic attacks the substantial influence was caused by an etiologic factor, that resulted to cerebral catastrophe. Reparative-restoration treatment by the ENT method decreased frequency of EA origin at patients with nontraumatic AS in 8,5 times compared to traumatic AS.